ANALISIS KEBUTUHAN AIR IRIGASI DENGAN SOFTWARE CROPWAT 8.0 DI DAERAH IRIGASI BELIMAU SAMARINDA - WARDANA, MUHAMMAD ALI (KURVA S JURNAL MAHASISWA, 2019)
Muhammad Ali Wardana, 2019, ANALYSIS OF IRRIGATION WATER REQUIREMENTS WITH CROPWAT 8.0 SOFTWARE IN VELVET IRRIGATION AREAS, Thesis, Civil Engineering Study Program, Faculty of Engineering, University August 17, 1945.Water is a natural resource that is very important for the survival of all living things. Water is also very necessary for industrial activities, fisheries, agriculture, and other businesses. In the use of water, there is often no caution in its use and utilization, so that efforts are needed to maintain a balance between the availability and demand of water through development, preservation, repair and protection. In the use of water, especially once again in terms of agriculture, in order to meet food needs and regional development.In meeting water needs, especially for water and rice fields, it is necessary to build irrigation systems and weir buildings. The need for water in the fields is then called the need for irrigation water. Irrigation is an effort to supply, regulate and dispose of irrigation water to support agriculture whose types include surface irrigation, swamp irrigation, underground water irrigation, pump irrigation and pond irrigation. The purpose of irrigation is to utilize available irrigation water correctly, efficiently and effectively so that agricultural productivity can increase as expected.In terms of calculations, the calculation of irrigation water needs is manually guided by Irrigation Planning Standards Planning Criteria for Irrigation Networks KP-01 2010, while Cropwat 8.0 is guided by FAO because CROPWAT is software developed by FAO.With the Cropwat 8.0 software calculation method, the results of the CWR Rice feature show that the maximum effective rainfall results in December are 47.8 mm/dec (47,800 liters/second/Ha). The maximum irrigation water demand occurred in October of 186.4 mm/dec (186,400 liters/second /Ha). For Palawija CWR, the maximum effective rainfall is 46.2 mm/dec (46,200 liters/second/Ha) in December. Whereas the maximum irrigation water requirement occurs in December of 19.1 mm/dec (19,100 liters /second/Ha).